Visual distractions for pediatric patients in a dental environment using eye-tracking technology: a cross-sectional study - Alhowra A. Alshaikh; Ghalia Y. Bhadila; Osama M. Felemban; Heba M. Elkhodary; Amani A. Al Tuwirqi (Clinical Oral Investigations, 2026)
Abstract Objective To evaluate visual attention patterns in anxious versus non-anxious children toward various environmental distractions in a dental clinic using eye-tracking technology and assess the impact of visual distractors on gaze behavior. Materials and methods This cross-sectional study, including 121 children 6–12 years of age. Anxiety levels were determined using the Children’s Fear Survey Schedule–Dental Subscale. Standardized operatory images, with and without distractors, were presented while eye-tracking metrics were recorded. Heatmaps were generated and group comparisons were performed using non-parametric tests. Results Nearly one-half (49.6%) of participants were classified as anxious who, in the absence of distractors, exhibited faster entry times and longer dwell times on dental instruments and handpieces than their non-anxious counterparts ( p < 0.001). Introduction of distractors significantly redirected gaze toward child-friendly elements, altered fixation sequences, and reduced revisits to clinical tools. Children in both groups consistently focused on clinicians’ eyes, with decorated masks attracting further attention. Conclusion Anxious children demonstrated distinct gaze patterns compared with their non-anxious peers, exhibiting faster orienting and altered engagement with dental instruments. Introduction of visual distractors significantly redirected attention toward child-friendly elements and away from anxiety-provoking stimuli, emphasizing the influence of anxiety on visual focus and the effectiveness of environmental modifications in improving the pediatric dental experience. Clinical relevance This study contributes to the design of anxiety-reducing pediatric dental environments by identifying elements that attract the visual attention of children. The presence of appropriate distractors within the pediatric dental clinic may help redirect children’s gaze away from clinical tools and instruments. These findings can inform the design and layout of pediatric dental clinics to enhance comfort and patient cooperation, ultimately improving the overall quality of pediatric dental care.